PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI TERHADAP PEMBENTUKAN KARAKTER (Penelitian di Kelas IX SMP Modern Riyadhul Jannah) - Syahid Bisri; Yunus Sopandi; Afif Nurseha; Endah RobatulAdawiyah (Jurnal Pendidikan Educandum, 2025)
The concept of Islamic Religious Education in a simple sense Education is often interpreted as a human effort to foster his personality in accordance with the values of society and culture. This study aims to analyse the effect of Islamic Religious Education (PAI) and Budi Pekerti learning on student character building at Riyadhul Jannah Modern Junior High School. Islamic Religious Education and Budi Pekerti are considered crucial in shaping the character of students who are morally upright and responsible. This study uses a quantitative approach with statistical analysis to test the influence of the two variables on student character building. The frequency of implementation of Islamic Religious Education subjects at Riyadhul Jannah Modern Junior High School shows a combination of formal curriculum and typical pesantren religion. Meanwhile, the frequency of the implementation of ethics at Riyadhul Jannah Modern Junior High School is in accordance with the middle theory because the phenomenon discussed focuses on the specific relationship and practice of implementing ethical values at school with its impact on the formation of student character. The results show that although PAI learning has an important role, its influence on student character building is not significant (T count = 0.716 < T table = 1.684). In contrast, Budi Pekerti was shown to have a significant influence (T count = 3.865 > T table = 1.684) on students' character building. Simultaneously, both PAI and Budi Pekerti provided a significant effect (T count = 3.865 > T table = 1.684) on students' character building.